Physicochemical analysis of free amino acid-based infant formula used in the treatment of cow's milk protein allergy (Research, Society and Development, 2021)
Allergy to cow's milk protein is an inflammatory, immunologically mediated disease that mainly affects the gastrointestinal tract and the skin. The general objective of the research is to analyze the quality profile of infant formulas based on free amino acids using physicochemical methods. This is an explanatory research, using an experimental method with a qualitative and quantitative approach, in which two brands of infant formula based on Free amino acids were analyzed. The samples were prepared as established by the manufacturer. The physicochemical methods used were, reconstitution/stability test, visual color test and hydrogen ionic potential analysis. In the reconstitution/stability test of the formulas, the two brands were stable after preparation, in the two types of water “filtered/boiled water and mineral water” and within the stipulated times. In the color test, the two brands showed a white/yellowish color after preparation, in both types of water and at all stipulated times. In the analysis of hydrogenionic potential, there was a difference between the two analyzed formulas. Formula 1 was more acidic and Formula 2 was more alkaline. Furthermore, over time there was a small reduction in pH values in both formulas and in both types of water. It was concluded that it was possible to carry out all the analyzes of the physicochemical parameters and that the two Infant Formulas based on free amino acids only presented small variations in the item of hydrogenionic potential. However, it is necessary to carry out other physical-chemical tests to guarantee the quality of the analyzed products.